An Experimentally Investigation Of Usability Of A Blend Of Tallow Methyl Ester And Diesel Fuel Substitution Of Diesel Fuel In Diesel Engines - Altun, Sehmus; Oner, Cengiz; Aydin, Huseyin; Yucel, Halit Lutfi (Gazi Univ, 2010)
Biodiesel fuels is one of the most attractive alternative fuels to reduce both emissions and petroleum based fuel consumption resulted from diesel engines. Therefore, the effects of biodiesel fuels on long-term engine operation and deposits in engine are considerably important, when biodiesel was evaluated as the alternative fuel for diesel engines. In this study, a 100 h engine test was performed on a single cylinder diesel engine using diesel fuel and tallow methyl ester as biodiesel fuel in order to compare the effects of the fuels on engine operation and deposits. The biodiesel was blended with 80 vol% diesel fuel and 20 vol % tallow methyl ester. Also, short-term engine performance and emissions were investigated and compared using both fuels. The test engine was disassembled before and after the experiment to determine the difference and clean carbon deposits. Experimental results were similar for both fuels in long-term engine tests, and indicated that the engine was satisfactorily operated for 100 hours with blend fuel. Deposits in engine at the end of the 100 h test were comparable in amount, but slightly different in color and adhesive, with the blend fuel when compared with those of diesel fuel. Besides, the blend fuel was comparable with the performance of diesel fuel and the exhaust emissions were lower than that of diesel fuel. It is concluded at the results of engine tests; the blend fuel can be a suitable alternative fuel for diesel engines to substitute diesel.
Keywords: Tallow methyl ester; Engine deposits; performance and emissions